Comparison of SSCP and DHPLC for the detection of LDLR mutations in a New Zealand cohort. - Bunn, C; Lintott, C; Scott, R; George, P (2002)
Familial hypercholesterolaemia (FH) is a common inherited disorder, associated with premature vascular disease. FH may be caused by many different mutations in the low density lipoprotein receptor (LDLR) gene, about 700 mutations have been described, most of which occur rarely and often only in single families. Although particular mutations are prevalent in certain ethnic groups, countries with heterogeneous population bases (such as NZ) may carry a wide variety of mutations; making a gene screening approach the appropriate first step for a mutation detection programme. We have compared SSCP with DHPLC to assess their effectiveness as methods for LDLR mutation detection. Although five novel LDLR mutations were detected by SSCP in patients with FH, DHPLC was more sensitive, with eight novel mutations detected. Six of these mutations (T392M, R419G, Y421N, 1206-1207delCT, 1872delC, and 1943delC) were clustered in exons 9 and 13 of the EGF precursor homology domain, one (679-680delAC) in the ligand binding domain (exon 4) and the eighth (P774H) in the membrane-spanning domain (exon 16). Twenty five mutations were identified in 35 patients in total. Of these, we were able to detect only 64% of mutations by SSCP even though all variants were detected by DHPLC. All patients are heterozygous for the mutations, which is consistent with the clinical phenotypes.